An informational video about clean coal technology's use of Davao City's Water resources a storyboard on the adventures of droplet inside a Coal Power Plant - Santos, Ma. Ferina P.
An Informal Video about Clean Coal Technology?s Use of Davao City?s Water Resources: A Storyboard on the Adventures of Droplet Inside a Coal Power Plant is a video production thesis that aimed to disseminate the current information about clean coal technology?s use of Davao City?s water resources to the consumers of electricity in Davao City. This production study recognized the need to address the lack of information among the general public of Davao City brought about by the insufficiency of Aboitiz Power?s existing public information campaign. Using Anthony Friedman?s Seven Step Method, I was able to create an informational material using the most appropriate medium and story concept that answered the objectives of this study completely. In creating the storyboard for the informational video, the proper mix of camera shots, camera angles, transitions between shots and the proper use of sound were applied in order to come up with an effective informational video. The final story concept of my informational video contains the journey of Droplet, a personified water droplet as the visual metaphor for water, having an adventure inside a coal power plant. I focused the whole story concept of the informational video on the process of how the coal power plant will use water. Highlighting the fact that the water used in the coal power plant will not come in contact with the coal or any other chemicals while inside the said plant because that was what Aboitiz Power failed to effectively disseminate to the consumers of electricity in Davao City. This study, therefore addressed this insufficiency of information among the consumers or the general public in Davao City
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts